Produção ilegal do espaço urbano : estudo de São José do Rio Preto - SP - Santos, Alessandra Cristina dos (Universidade Federal de São Carlos, 2007)
Urban occupation in rural areas by settlements without approval is a growing phenomenon in São Paulo State medium-sized cities, and so far, few works have been carried out about these illegal settlements out of large cities. Such theme-based studies are relevant due to the resulting occurrence of high magnitude negative impacts. The present paper deals with the expansion process of illegal settlements both irregular and unauthorized ones , having as a study case the city of São José do Rio Preto. The aim is to study the phenomenon of illegal settlements production in this city, through their identification and qualification, also the search of causal relationship of this production, analyzing the legal situation and the relationship between this production and public policies and the real estate market dynamics and finally identifying and evaluating the resulting socialenvironmental impacts.
Keywords: Planejamento urbano; Loteamento irregular; Cidades médias; São José do Rio Preto (SP); Ilegalidade; Mercado de terras; Espraiamento; Illegality; Medium-sized cities; Land market; Spreading; ENGENHARIAS